Reliability Metric based Patient Centred Activity Recognition for Smart Healthcare Monitoring - G.Yamini, Dr.Gopinath Ganapathy (International Journal of Advanced Science and Technology, 2020)
In recent years, increasing attention has been given towards reliability metrics in the healthcare systems. This reliability metric helps to evaluate the impact on healthcare monitoring systems redesign. Healthcare KPIs or metrics are the special key indicators that optimize the healthcare process by monitoring and analyzing healthcare data, which promotes a reliable measurement with the increase patient’s satisfaction. These metrics are reliable key indicators and attained a huge impact with the healthcare monitoring system as they play a significant role with IoT based effective and non-effective healthcare monitoring system classification. But,there is room for improvements in analytical methodologies, data collection, and activity recognition with reliability measurement implementation. This could enhance the reliability of the healthcare monitoring system that promotes major opportunities to the policy makers with the reliable measurement. The proposed reliabilitydriven activity recognition solves the challenges of the real-life scenario of patient monitoring.